Identification of novel HIV-1-derived HLA-E-binding peptides - Hannoun, Z; Lin, Z; Brackenridge, S; Kuse, N; Akahoshi, T; Borthwick, N; McMichael, A; Murakoshi, H; Takiguchi, M; Hanke, T (Elsevier, 2018)
Non-classical class Ib MHC-E molecule is becoming an increasingly interesting component of the immune response. It is involved in both the adaptive and innate immune responses to several chronic infections including HIV-1 and, under very specific circumstances, likely mediated a unique vaccine protection of rhesus macaques against pathogenic SIV challenge. Despite being recently in the spotlight for HIV-1 vaccine development, to date there is only one reported human leukocyte antigen (HLA)-E-binding peptide derived from HIV-1. In an effort to help start understanding the possible functions of HLA-E in HIV-1 infection, we determined novel HLA-E binding peptides derived from HIV-1 Gag, Pol and Vif proteins. These peptides were identified in three independent assays, all quantifying cell-surface stabilization of HLA-E*01:01 or HLA-E*01:03 molecules upon peptide binding, which was detected by HLA-E-specific monoclonal antibody and flow cytometry. Thus, following initial screen of over 400 HIV-1-derived 15-mer peptides, 4 novel 9-mer peptides PM9, RL9, RV9 and TP9 derived from 15-mer binders specifically stabilized surface expression of HLA-E*01:03 on the cell surface in two separate assays and 5 other binding candidates EI9, MD9, NR9, QF9 and YG9 gave a binding signal in only one of the two assays, but not both. Overall, we have expanded the current knowledge of HIV-1-derived target peptides stabilizing HLA-E cell-surface expression from 1 to 5, thus broadening inroads for future studies. This is a small, but significant contribution towards studying the fine mechanisms behind HLA-E actions and their possible use in development of a new kind of vaccines.